Trends on Friendly Disability Services: A Bibliometric Review - Dwi Martiningsih (Westscience Press, 2023)
Accessing public services and carrying out regular tasks can be difficult for those with disabilities. Disability-friendly services are important to them. This is due to the fact that there are equal rights for all human beings in all aspects of life. To get a structural picture and provide significant insights about disability-friendly services, this study conducted a bibliometric analysis. We used the Scopus database, searching for the keyword